Dramatic enhancement of organics degradation and electricity generation via strengthening superoxide radical by using a novel 3D AQS/PPy-GF cathode. (15th November 2017) - Zhang, Yan; Li, Jinhua; Bai, Jing; Li, Linsen; Xia, Ligang; Chen, Shuai; Zhou, Baoxue
Abstract: A dramatic enhancement of organics degradation and electricity generation has been achieved in a wastewater fuel cell (WFC) system via strengthening superoxide radical with radical chain reaction by using a novel 3D anthraquinone/polypyrrole modified graphite felt (AQS/PPy-GF) cathode. The AQS/PPy-GF was synthesized by one-pot electrochemical polymerization method and used to in-situ generate superoxide radical by reducing oxygen under self-imposed electric field. Results showed that methyl orange (MO) were effectively degraded in AQS/PPy-GF/Fe 2+ system with a high apparent rate constant (0.0677 min −1 ), which was 3.9 times that (0.0174 min −1 ) in the Pt/Fe 2+ system and even 9.4 times that (0.0072 min −1 ) in the traditional WFC system (without Fe 2+ ). Meanwhile, it showed a superior performance for electricity generation and the maximum power density output (1.130 mW cm −2 ) was nearly 3.3 times and 5.0 times higher, respectively, when compared with the Pt/Fe 2+ system and traditional WFC. This dramatic advance was attributed to 3D AQS/PPy-GF cathode which produces more O2 − via one-electron reduction process. The presence of O2 − cannot only directly contribute to MO degradation, but also promotes the final complete mineralization by turning itself to OH. Additionally, O2 − accelerates the Fe 2+ /Fe 3+ couple cycling, thus avoiding continuous addition of any external ferrous ions. Inhibition and probe studies were conducted to ascertain the role of several radicals (OH and O2 − ) on the MO degradation. Superoxide radicals were considered as the primary reactive oxidants, and the degradation mechanism of MO was proposed. The proposed WFC system provides a more economical and efficient way for energy recovery and wastewater treatment. Graphical abstract: Highlights: A new wastewater fuel cell was constructed by using a novel 3D AQS/PPy-GF cathode. The WFC has dramatic enhancements of organics degradation and electricity generation. The novel 3D AQS/PPy-GF cathode strengthens the yield of superoxide radical. O2 − accelerates Fe 2+ /Fe 3+ cycle for organics degradation and electricity production.